Preparation for an international sport event: The promotional strategies of 2009 Kaohsiung World Games - Chen, S.; Dick, R.; McNabb, A. (The Sport Journal, 2010)
Abstract This investigation presented administrative and marketing-related information on Kaohsiung City`s preparation for the 2009 World Games. The presented information was allocated through an extensive literature review on secondary sources, personal interviews, and observations from fall of 2008 to summer of 2009. Promotional strategies and activities, projected financial and sales data, reports on constructions, and issues and challenges related to the Games were further analyzed. The study further discussed the "not-for-profit" approach that was practiced by many East Asian Countries to gain international recognition and promote patriotism while hosting a major sport event.